Pemanfaatan Deleterious rhizobacteria Untuk Mengendalikan Gulma Utama Tanaman Padi di Kabupaten Jember - Yogi Ardhi Cahyadi; Saifuddin Hasjim (Jurnal Pengendalian Hayati, 2019)
The purpose of the study was to determine the characteristics of plant pathogens from Deleterious rhizobacteria (DRB) that have the potential as biological control agents in the main weeds of rice plants. This research was conducted in April-August 2019 at the Plant Protection Laboratory, Faculty of Agriculture, University of Jember. Rhizobacteria sampling was taken from rice fields in Mayang District. Weed sampling technique is done by purposive randomized sampling. The collections of pathogen-infected weeds are then isolated using laminar airflow and identified through several test stages. DRB exploration results obtained by two microorganisms that can be used as biological control to control the main weeds of rice plants from the Pseudomonas group, they are P. syringae pv. glycinea (M1) and P. syringae pv. syringae (M2). Based on the identification of the two isolates morphologically that (M1) has a greenish-white color with a flat edge type. Whereas the isolate code (M2) has a yellowish murky white color with a rather irregular jagged edge type. However, the two isolates have similarities in spherical shape. The physiological observations of both M1 and M2 isolate from the Catalase test, fluorescent pigments produce gram-positive (+) while gram tests produce gram-negative (-). The conclusion of this research is the characterization of P. syringae pv. glycinea (M1) and P. syringae pv. syringae (M2) both morphologically and physiologically.